Ethanol production from sugar cane molasses and different strains of yeast (SCIÉNDO INGENIUM, 2022)
The application of different sugar cane molasses conditions (yeast strain, antibiotic concentration and molasses pH) was aimed at obtaining the highest ethanol yield. In ethanol production, a 3x3x3 factorial design was used with 3 replicates per treatment, with antibiotic concentration levels: 10 ppm, 15 ppm and 20 ppm; pH: 4.6, 4.8 and 5.0 and yeast strains: Fleish-mann, Red Star and Fermipan Brown. The process applied involved molasses conditioning, fermentation and distillation. The results showed that the maximum ethanol yield (314.13 ± 8.77 L/MT of molasses) was obtained with the yeast strain Saccharomyces cerevisiae Fermipan Brown at pH 4.8 and antibiotic concentration of 15 ppm. In conclusion, the proposed treatment was shown to have a higher productivity in relation to the other proposed methods.
Keywords: Fermentation; performance; molasses; ethyl alcohol; yeast